Transurethral resection of bladder neck in female patients with neurogenic bladder - Murayama, K (Hinyokika kiyo. Acta urologica Japonica, 1988)
Transurethral resection of the bladder neck was performed in 6 female patients with neurogenic bladders who presented with a large volume of residual urine and bladder neck obstruction on voiding cystourethrography without detrusor hyperreflexia on cystometry. In 4 of the patients, transurethral sphincterotomy was performed concomitantly. Five of the patients demonstrated significant improvement in bladder emptying and 4 did not need self-catheterization. No complications of the operation were observed